Clinical features and outcomes of tuberculosis in transplant recipients as compared with the general population: a retrospective matched cohort study. (July 2015) - Benito, N.; García-Vázquez, E.; Horcajada, J.P.; González, J.; Oppenheimer, F.; Cofán, F.; Ricart, M.J.; Rimola, A.; Navasa, M.; Rovira, M.; Roig, E.; Pérez-Villa, F.; et al.
Abstract: There are no previous studies comparing tuberculosis in transplant recipients (TRs) with other hosts. We compared the characteristics and outcomes of tuberculosis in TRs and patients from the general population. Twenty-two TRs who developed tuberculosis from 1996 through 2010 at a tertiary hospital were included. Each TR was matched by age, gender and year of diagnosis with four controls selected from among non-TR non-human immunodeficiency virus patients with tuberculosis. TRs (21 patients, 96%) had more factors predisposing to tuberculosis than non-TRs (33, 38%) (p <0.001). Pulmonary tuberculosis was more common in non-TRs (77 (88%) vs. 12 TRs (55%); p 0.001); disseminated tuberculosis was more frequent in TRs (five (23%) vs. four non-TRs (5%); p 0.005). Time from clinical suspicion of tuberculosis to definitive diagnosis was longer in TRs (median of 14 days) than in non-TRs (median of 0 days) (p <0.001), and invasive procedures were more often required (12 (55%) TRs and 15 (17%) non-TRs, respectively; p 0.001). Tuberculosis was diagnosed post-mortem in three TRs (14%) and in no non-TRs (p <0.001). Rates of toxicity associated with antituberculous therapy were 38% in TRs (six patients) and 10% (seven patients) in non-TRs (p 0.014). Tuberculosis-related mortality rates in TRs and non-TRs were 18% and 6%, respectively (p 0.057). The adjusted Cox regression analysis showed that the only predictor of tuberculosis-related mortality was a higher number of organs with tuberculosis involvement (adjusted hazard ratio 8.6; 95% CI 1.2–63). In conclusion, manifestations of tuberculosis in TRs differ from those in normal hosts. Post-transplant tuberculosis resists timely diagnosis, and is associated with a higher risk of death before a diagnosis can be made.